Pengaruh Digital marketing Terhadap Brand awareness Produk Fashion Jiniso pada Mahasiswa Program Studi Manajemen UKI Toraja - Ita Rante Pasang; Lisa Kurniasari Wibisono; Astriwati Biringkanae (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the influence of digital marketing on brand awareness of Jiniso fashion products among UKI Toraja management study program students. This research data was obtained from distributing questionnaires to 43 students of the UKI Toraja management study program. This research uses quantitative research methods. Data were analyzed using SPSS version 26. The results of this research show that digital marketing has a positive and significant effect on brand awareness. This is proven by the results of a simple linear regression test Y= 11,687+ 0.829X with a calculated t value > t table, namely 6.126 > 2.018 and a significant value < 0.05, namely 0.000. If we look at the coefficient of determination, it shows that the R square value is 0.478 or 47.8% with the remaining 52.2% being influenced by other variables not found in this study.